Sosialisasi Pencegahan Demam Berdarah di Sogo Kabupaten Semarang - Purwaningsih, Puji; Chaerijah, Zumrotul; Suwanti; Nurvina Khasanah; Nurlita Makhyasari; Gipta Galih Widodo; Abdul Wakhid (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Socialization of dengue fever prevention is a process of learning to recognize and adapt to the environment that causes dengue hemorrhagic fever transmission. Problems found from the results of interviews with leaders obtained data for the last 2 months (May 2024) there were 4 residents who suffered from DHF The head of the RT said that in Sogo Hamlet there was only 1 active cadre, community leaders said that JUMANTIK monitoring had been carried out by cadres from Sigade hamlet RT 06 but the activity had not been running since 1 year ago, Puskesmas officers said there were several residents who did not report to the Puskesmas when exposed to DHF. The purpose of the activity is to increase changes in the aspects of behavior, attitudes, and behavior of the community as a prevention of DHF. The method used begins with observation and giving questionnaires to be filled in regarding questions about dengue hemorrhagic fever, after the data is found, a nursing diagnosis is formulated which is followed by network implementation activities with the Lerep Health Center. Analysis of pre post knowledge using the Wilcoxon test obtained data p value (0.001) shows that there is an increase in knowledge between before and after socialization.   ABSTRAK Sosialisasi pencegahan demam berdarah merupakan suatu proses belajar mengenal dan menyesuaikan diri dengan lingkungan penyebab penularan demam berdarah dengue. Permasalan yang ditemukan dari hasil wawancara tokoh didapatkan data 2 bulan terakhir (Mei 2024) terdapat 4 warga yang menderita DBD Ketua RT mengatakan di Dusun Sogo hanya terdapat 1 Kader aktif ,tokoh masyarakat mengatakan untuk sudah pernah dilakukan pemantauan JUMANTIK oleh Kader dari  dusun Sigade RT 06 tetapi kegiatan tersebut sudah tidak berjalan sejak 1 tahun yang lalu, petugas Puskesmas mengatakan terdapat beberapa warga yang tidak lapor ke pihak Puskesmas ketika terkena DBD. Tujuan kegiatan untuk menambah merubah aspek perilaku, sikap, perilaku masyarakat sebagai pencegahan DBD. Metode yang digunakan diawali dengan observasi dan pemberian angket untuk diisi berkaitan pertanyaan-pertanyaan seputar demam berdarah dengue, setelah ditemukan data kemudian dirumuskan suatu diagnosis keperawatan yang diikuti dengan kegiatan implementasi jejaring dengan Puskesmas lerep. Analisis pre post pengetahuan menggunakan uji Wilcoxon didapatkan data p value (0,001) menunjukan bahwa ada peningkatan pengetahuan antara sebelum dan sesudah sosialisasi.